2013
DOI: 10.1080/07399332.2012.721414
|View full text |Cite
|
Sign up to set email alerts
|

The Context of Condom Use Among Young Adults in the Philippines: Implications for HIV Prevention

Abstract: We examine current perceptions and constraints surrounding condom use among young adults in the Philippines to garner a deeper contextual understanding of this aspect of HIV prevention within Filipino society. Through thematic analysis of focus group data, we found three broad themes, all of which included societal and individual barriers to using condoms. The findings may provide insight for similar settings that have strong religious influences on society. To strengthen HIV prevention efforts in such setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 22 publications
7
45
0
Order By: Relevance
“…Although this study did not look at the cost, availability and accessability of the condom vis a vis attitude of the respondents towards condom use, it is possible that high cost and scarcity of the condoms could probably discourage the use of it. This hypothesis is in agreement with the study by Lucea et al (2013), which noted that some of the barriers to condom use were the cost, availability of condoms and their accessibility.…”
Section: Discussionsupporting
confidence: 92%
“…Although this study did not look at the cost, availability and accessability of the condom vis a vis attitude of the respondents towards condom use, it is possible that high cost and scarcity of the condoms could probably discourage the use of it. This hypothesis is in agreement with the study by Lucea et al (2013), which noted that some of the barriers to condom use were the cost, availability of condoms and their accessibility.…”
Section: Discussionsupporting
confidence: 92%
“…Certain studies have also reported that suggestion to use a condom can lead to doubts of sexual promiscuity among partners, especially in a husband and wife relationship. 15 Workers with low education, older age, female gender and those married living with their spouse should be targeted for specific educational interventions. 16 Similarly, occupationally high risk groups such as lorry drivers, immigrants from other states should be encouraged and educated about proper condom usage.…”
Section: Discussionmentioning
confidence: 99%
“…Filipino daughters are expected to follow the "ideal" female virtues, including maintaining virginity until after marriage (Alampay & Jocson, 2011;Chen et al, 2010;Nadal, 2009). In the Philippines, unmarried couples, in general, use condoms for contraception rather than disease prevention (Lucea, Hindin, Gultiano, Kub, & Rose, 2013). Unmarried couples often hide sexual relationships from their parents (Lucea et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the Philippines, unmarried couples, in general, use condoms for contraception rather than disease prevention (Lucea, Hindin, Gultiano, Kub, & Rose, 2013). Unmarried couples often hide sexual relationships from their parents (Lucea et al, 2013).…”
Section: Discussionmentioning
confidence: 99%